Pemasaran di Perguruan Tinggi - Prabowo, Sugeng Listyo (ULUL ALBAB Jurnal Studi Islam, 2005)
Higher education (university) as non profit institution service as well as another institution extremely need marketing. In this competitive era and required highly independency, the existence of customer is necessary. For this reason, management in university have to prove and build image in society that his institution able to fulfill the need and the hope of the society. Marketing in higher education mostly understood as selling and promotion were as marketing is more widely than about of two terminology above mention. Misunderstanding of marketing as usually happen university became "uncomfortable ’’ to use the word marketing in university, because marketing in university is social institution that move in the field of education, that in one hand university have to develop social mission, but in the other hand the university has to get the student suit to the condition of capacity, because basically the essence of university is the existence of the student that will be educated and developed whether in cognitive, affective, as well as psychomotor domain.